2020
DOI: 10.1038/s41388-020-01395-9
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous toxic metabolites and implications in cancer therapy

Abstract: It is well recognized that many metabolic enzymes play essential roles in cancer cells in producing building blocks such as nucleotides, which are required in greater amounts due to their increased proliferation. On the other hand, the significance of enzymes in preventing the accumulation of their substrates is less recognized. Here, we outline the evidence and underlying mechanisms for how many metabolites normally produced in cells are highly toxic, such as metabolites containing reactive groups (e.g., meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 120 publications
1
21
0
2
Order By: Relevance
“…High extracellular stability; responds quickly and releases genes quickly inside the cell Lack of specificity and precision for differences in intracellular and extracellular concentrations of GSH in both normal and tumor cells; Non-selective response delivery may lead to unexpected release and related side effects; The reductive property of disulfide bond may be adversely affected by steric hindrance of a nanocarrier [ 12,119] Enzyme Enzymatic reaction is rapid and reaction conditions are mild; enzymes are selective to substrates with high selectivity and specificity Development of enzyme-responsive polymer components, nanoparticles and hydrogels is still in its infancy; Enzymes at nontarget sites or similar substrates of the same family of enzymes may also trigger cargo release [ 127] ROS Responds according to different ROS levels in the tissue Biocompatibility, accuracy and sensitivity of stimulus response need to be further improved; In vivo research is still in its infancy [ 142] ATP ATP exists in both intracellular and extracellular tissues, intracellular concentration is much higher than extracellular concentration particularly in tumor cells Nonspecific distribution in entire organ/tissues and lack of spatial resolution [ 205] Hypoxia High sensitivity, can target the deep hypoxic region of the tumor…”
Section: Redoxmentioning
confidence: 99%
“…High extracellular stability; responds quickly and releases genes quickly inside the cell Lack of specificity and precision for differences in intracellular and extracellular concentrations of GSH in both normal and tumor cells; Non-selective response delivery may lead to unexpected release and related side effects; The reductive property of disulfide bond may be adversely affected by steric hindrance of a nanocarrier [ 12,119] Enzyme Enzymatic reaction is rapid and reaction conditions are mild; enzymes are selective to substrates with high selectivity and specificity Development of enzyme-responsive polymer components, nanoparticles and hydrogels is still in its infancy; Enzymes at nontarget sites or similar substrates of the same family of enzymes may also trigger cargo release [ 127] ROS Responds according to different ROS levels in the tissue Biocompatibility, accuracy and sensitivity of stimulus response need to be further improved; In vivo research is still in its infancy [ 142] ATP ATP exists in both intracellular and extracellular tissues, intracellular concentration is much higher than extracellular concentration particularly in tumor cells Nonspecific distribution in entire organ/tissues and lack of spatial resolution [ 205] Hypoxia High sensitivity, can target the deep hypoxic region of the tumor…”
Section: Redoxmentioning
confidence: 99%
“…Endogenous metabolites are defined as substrates or products of approximately one thousand nine hundred metabolic enzymes encoded in our genome [14][15][16]. There are several studies showing that most of these metabolites are toxic.…”
Section: Endogenous Metabolitesmentioning
confidence: 99%
“…Intermediary metabolites are responsible for maintaining organ homeostasis, and their signaling functions are involved in the modulation of cell function [ 1 ]. Numerous studies have found that internal metabolites perform an important part in the progress of several diseases, such as Type 2 diabetes [ 2 ] cancers [ 3 4 ] atherosclerosis [ 5 6 ] cardiac disease [ 7 8 ] chronic kidney disease [ 9 ] and Alzheimer disease [ 10 ]. These natural chemical compounds are rather cheap and simple to manufacture in huge quantities.…”
Section: Introductionmentioning
confidence: 99%